Why Union Activists Write Good Stories - Worthen, Helena (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2013)
The representative structure of a union is a maze which, when travelled as a narrative, has drama at every turn. It sets up expectations, pits good against evil, involves many characters with different interests, keeps the clock ticking, and offers opportunities for happy endings (and disappointments) at every level. Union members who are not experienced writers can produce good stories by writing about their lives at work and in the union.